Improvement Proposal for Operational Safety in PT. Kereta Api Indonesia (Persero) Using People Management Approach - Firstyadhika, Irdra; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2012)
Health and Safety at work is a thought and effort to ensure the integrity and perfection of both physical and spiritual labor in particular, and human beings in general, and cultural work towards fair and prosperous society (Mangkunegara, 2002). Another source said that safety is a series of efforts to create a work atmosphere that is safe and peaceful for those employees who worked at the company in question (Suma'mur, 2001).KNKT (National Committee on Transportation Accidents of Indonesia) in the event of the national railway safety held on March 2011, concluded: Safety is imposible without leadership, without safety leadership is imposible. Enforcement of laws and regulations that are less consistent or incomplete rules on safety, inadequate training, lack of rewards and punishments, regulations that need to be replaced or adjusted, transportation infrastructure that does not comply with the demands, means of transportation that do not meet the airworthiness standards and technical requirements, and lacking even the lack of coordination may be the underlying cause of the accident.The model of this research discusses that good people management companies have a positive impact to the operational safety performance. Good people management is influenced by a company's management commitment, safety committee involvement, leadership, training and development, communication and control, and performance management. While operational safety performance was favorably impacted by a solid safety culture, company reputation, preventive action, and the low incident.The results of the research showed that the predictors of good human management company with safety performance has a strong influence; then communication and control, performance management, and the involvement of the safety committee are the variables that were highly influential. Gap analysis using descriptive analysis found that there are several indicators that have a low value in the eye of employees. Keyword‒ safety, accidents, people management, state owned company, transformation, Indonesian state owned company